Synthesis of Phosphoric Acid Ester-based Flame Retardants and their Application via Sol-Gel Process to Enhance Flame Retardancy of Cotton Fabric - Narwal, Laxmi; Dahiya, J.B. (Asian Journal of Chemistry, 2025)
In order to enhance the flame retardancy of cotton fabric and expand it use in regions with strict fire safety regulations, the phosphoric acid esters-based organic compounds such as diphosphoric acid ethyleneglycol ester (diPEG), triphosphoric acid glycerol ester (triPGE), and tetraphosphoric acid pentaerythritol ester (tetraPPE) were synthesized and characterized by 1H-NMR, 31P-NMR and HRMS. The cotton fabric was treated with these compounds and aminopropyltriethoxysilane (APTES) a sol-gel precursor by using sol-gel process. FTIR spectrum of treated fabric shows additional peaks at 1240 (P=O), 1044 (Si-O-Si) and 794 cm-1 (Si-O), which shows the presence of flame retardant coating on fabric. Thermogravimetric analysis was employed to conduct the change in path of thermal degradation of treated cotton fabric. The behavior of flame retardancy was assessed through auto flammability and limiting oxygen index examinations. The treated cotton fabric exhibits outstanding flame retardant properties during combustion and are extinguished promptly once the ignition is eliminated. The limiting oxygen index value of the cotton fabric after treatment with tetraPPE/APTES flame retardant reached 38.3%, which is sufficiently above the flame retardant value of about 27%. Morphological structures of fabric were also investigated using FESEM.